Experiencias docentes en la enseñanza de Física - Ordoñez Celi, Johanna Socorro (2024)
The fundamental basis of the teaching experience is to achieve academic excellence in the teaching-learning process; it is the development of guidelines that the teacher acquires in order to make them available to the educational community. The important elements involved in this process must be considered, such as: the teacher and his/her methodology; the structure of the knowledge defined in the curricula, and the context in which the student develops. This paper describes what characterizes a successful teaching experience in the teaching of Physics, taking into consideration specifically the first year of the Unified General Baccalaureate of the curricular block 1: Movement and Force. A qualitative research of documentary design is presented, using research techniques such as the bibliographic file. This research establishes the importance for teachers to have educational processes that meet the learning needs of students, being a subject that requires that theory and practice are closely related in order to develop experimentation mechanisms, emphasizing that the experience that the teaching professional can obtain also depends on continuous training.